Implementing of Merdeka Curriculum; How Does School in Border Region Deal with it? (A Case Study of SMA Negeri 1 Putussibau in Academic Year 2022/2023) - Ednivia Elmanita Yopa Pratiwi; Dedi Irwan; Sahrawi, Sahrawi; Marsa Ayu Tira (Journal of English Language Teaching and Education (JELTE), 2025)
This research aims to describe how SMA Negeri 1 Putussibau implements the Merdeka Curriculum. The study employs a descriptive qualitative approach using a case study method. Data were collected through interviews and documentation involving the Principal, Vice Principal for Curriculum Affairs, and English teachers. Data analysis was conducted using the triangulation technique by Miles and Huberman. The findings reveal progress in the implementation of the Merdeka Curriculum, challenges encountered, and the impacts experienced from its application.   **Keywords:** Implementation, Merdeka Curriculum, SMA Negeri 1 Putussibau.